Ojcowie w opowiadaniach o patriarchach w Rdz 12-50 - Pawłowski, Zdzisław (Verbum Vitae, 2011)
The Book of Genesis tells a story about three fathers: Abraham, Isaac and Jacob. To be a father for Abraham is first to expect a child for a long time, then to follow the words of promise God speaks to him, especially the promise of a son. When Ishmael and Isaac have been born to him, his father affections are put to the tests. Ishmael has to be sent away along with his mother Hagar. Then, God commands him to sacrifice his now only son, Isaac. When Isaac himself was old and could not see, he was blinded by his desire for the venison stew, Esau used to prepare for him, but eventually he was corrected by his wife Rebekah who gained his blessing for Jacob, the son she loved. Finally, Jacob is the most experienced father. His love for Joseph and then after his alleged death, for his youngest son Benjamin, proved to be strong enough and stood the test of time.